2019
DOI: 10.15421/021962
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of microstructure of the suprarenal glands of rabbits with different types of autonomic tone

Abstract: The article investigates the structure of the suprarenal (adrenal) glands of male rabbits (Oryctolagus cuniculus), in which, on the basis of electrocardiographic and variational-pulsometric studies, different types of autonomic tone were observed. This allowed the animals to be divided into three groups: 1) sympathicotonic rabbits; 2) normotonic rabbits; 3) parasympathicotonic rabbits. The animals of the first two groups were characterized by almost the same body weight, while weight of the rabbits of the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
2
0
4
Order By: Relevance
“…Despite a large number of studies, we have not found any data that would prove the effect of different tonus of the autonomic nervous system on the morphology of the thyroid gland of rabbits. At the same time, a similar effect was established on the structure of the adrenal gland (Zakrevska & Tybinka, 2019). Studying this issue was the aim of our research.…”
Section: Introductionmentioning
confidence: 65%
“…Despite a large number of studies, we have not found any data that would prove the effect of different tonus of the autonomic nervous system on the morphology of the thyroid gland of rabbits. At the same time, a similar effect was established on the structure of the adrenal gland (Zakrevska & Tybinka, 2019). Studying this issue was the aim of our research.…”
Section: Introductionmentioning
confidence: 65%
“…Надниркова залоза є периферичним органом ендокринної системи, гормони якої впливають на розвиток органів, на водний, білковий, жировий, вуглеводний і мінеральний обміни, стійкість організму до інфекцій, інтоксикації, низької та високої температур, стресфакторів тощо (Matos, 2008). Надниркова залоза хребетних тварин за морфологічними ознаками є найбільш варіабельною ендокринною залозою, яка вирізняється особливостями макро -і мікроскопічної будови (Moawad & Randa, 2017;Zakrevska & Tybinka, 2019;Kot & Prokopenko, 2020). Аналіз наукової літератури показав, що відомості про дослідження надниркової залози в історичному аспекті є поодинокими та охоплюють відносно короткі хронологічні періоди (Luppova & Fedotov, 2009;Rybakov, 2018).…”
Section: вступunclassified
“…Фундаментальною і прикладною проблемою сучасної біології, гуманної та ветеринарної медицини є дослідження закономірностей розвитку, будови та функціонування органів ендокринної системи, оскільки остання разом з нервовою системою регулює та контролює всі процеси життєдіяльності організму (Parker et al, 2011;Zakrevska & Tybinka, 2019).…”
Section: вступunclassified
“…За морфологічними ознаками надниркова залоза є однією з найбільш варіабельних ендокринних залоз хребетних тварин (Barszcz et al, 2016;Zakrevska & Tybinka, 2019). Для птахів характерне видове різноманіття форми надниркової залози і ряд особливостей будови її паренхіми (Kober et al, 2012;Moawad & Randa, 2017).…”
Section: вступunclassified
See 1 more Smart Citation